Strategies for the Use of Oseltamivir and Zanamivir during Pandemic Outbreaks - Elsa Hansen; Troy Day; Julien Arino; Jianhong Wu; Seyed M Moghadas (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The use of neuraminidase inhibitors (oseltamivir and zanamivir) for the treatment of ill individuals has been an important intervention during the 2009 H1N1 pandemic. However, the emergence and spread of drug resistance remains a major concern and, therefore, optimizing antiviral strategies is crucial to retain the long-term effectiveness of these pharmaceutical interventions.